Pyelonephritis and Bacteremia Caused by Klebsiella variicola following Renal Transplantation - Cody Lo; Shazia Masud; Gregory D. Deans (Case Reports in Infectious Diseases)
Klebsiella variicola (K. variicola) is a Gram-negative organism genetically similar to Klebsiella pneumoniae (K. pneumoniae) that can cause a variety of diseases in humans. Bacteremia due to K. variicola is associated with a higher mortality rate than bacteremia with K. pneumoniae. Here, we describe a 65-year-old woman who developed pyelonephritis 2 months after receiving a renal transplantation following a longstanding history of end-stage renal disease secondary to polycystic kidney disease. Her creatinine on admission was unchanged from her posttransplant baseline, and an abdominal CT scan showed inflammatory changes around the transplanted kidney that were suggestive of an infection rather than allograft rejection. She was initially treated empirically with meropenem given a history of extended-spectrum beta-lactamase- (ESBL-) producing E. coli bacteriuria. After a day of therapy with meropenem, her therapy was streamlined based on culture results to ceftriaxone. She continued to improve, her kidney function remained stable, and she was prescribed oral ciprofloxacin to complete a 14-day total course of antibiotics. This case is the first reported instance of K. variicola bacteremia associated with pyelonephritis in a renal transplant recipient. Hospitalization with acute pyelonephritis within the first year following kidney transplant is common and is associated with increased risk of graft loss and mortality. However, K. variicola is not a commonly known organism to cause this infection. Despite the risk of allograft failure in this circumstance, this patient was successfully treated with a 14-day course of antibiotic therapy.